The changing nature of the international business field, and the progress of JIBS - Cantwell, John; Brannen, Mary Yoko (Journal of International Business Studies, 2016)
The Journal of International Business Studies (JIBS) is a journal with a high academic standing, and the leading journal in the field of international business (IB) research. It has become more open to new authors and to a wider range of IB scholarship. IB scholars study cross-border aspects of business activity. Some recent JIBS special issues have facilitated certain innovative new streams of IB research. Both the authors and the reviewers of the journal have become substantially more geographically diverse recently.